• Matéria: Matemática
  • Autor: victorgabriel17325
  • Perguntado 6 anos atrás

3- Qual o resultado de (x2 - 5x + 6) - (5x + 6)
a) x2 - 10x + 12
b) x2 - 10x
c) x2 + 4x - 12
d) x-63 ?????,​

Respostas

respondido por: leticiagonzaga467
1

Resposta:

letra ( b)

Explicação passo-a-passo:

x2 - 10x

espero ter ajudado!

respondido por: Makaveli1996
0

Oie, Td Bom?!

■ Resposta: Opção B.

 = (x {}^{2}  - 5x + 6) - (5x + 6)

 = x {}^{2}  - 5x + 6 - 5x - 6

 = x {}^{2}  - 5x - 5x

 = x {}^{2}  - 10x

Att. Makaveli1996

Perguntas similares